The Relationship Between Work Environment and Work Motivation on the Performance of Outsourced Employees at PT Kinarya in Harmony with The Device - Rohmad Hartono; Titin Hargyatni (Green Inflation: International Journal of Management and Strategic Business Leadership, 2026)
This study aims to analyze the influence of work environment and work motivation on the performance of outsourced employees at PT Kinarya Selaras Piranti. Phenomena in the field show the challenges of supervisory dualism and operational constraints, such as a difficult reimbursement system, which is suspected to affect productivity. The research method used was a quantitative approach with a saturated sampling technique (census) of 87 respondents. Data were collected through a digital questionnaire and analyzed using multiple linear regression through SPSS software. The results of the study showed that partially, the work environment had a positive and significant effect on employee performance (Sig. < 0.001). Similarly, work motivation has a positive and partially significant influence (Sig. < 0.001). Simultaneously, these two variables have a significant effect on performance with a determination coefficient value (R2) of 92.7%. This indicates that optimizing physical and non-physical conditions and meeting the psychological needs of employees are crucial factors in increasing work effectiveness in the outsourcing services sector.